Chem-USG Learning Media to Increase Students' Learning Interest in High School Chemical Equilibrium Material: A Case Study - Pradita, Pingky Nirmala; Lutfi, Achmad (Universitas Pendidikan Mandalika, 2025)
The aim of this research is to obtain Chem-USG learning media which is feasible to use in learning high school chemical equilibrium material to increase students' learning interest. The type of research used is research and development (R&D) with the 4D development model but only until the third stage. The stages carried out by researchers are define, design, and develop. The data collection techniques used by researchers are interviews, observations, questionnaires, and tests, while the data analysis used is quantitative descriptive. Validity is based on the learning media validation questionnaire. Practicality is based on activity observations and student response questionnaires. Effectiveness is based on a questionnaire of learning interest and student learning outcomes. The validation result of learning media yielded mode scores 3 and 4 with valid categories. At the trial stage, the average percentage score on the activity observation results was 80%-100% with a good category, and received good responses from students with mode scores of 3 and 4 with good categories so that Chem-USG media could be declared practical. And obtained an increase in the percentage of students' learning interest on the post-learning interest questionnaire reached above 80% with a good category and supported by improved student learning outcomes so that make the Chem-USG media effective. So, based on the results obtained, Chem-USG learning media can be said to be feasible to use to increase students' interest in learning high school equilibrium material because it meets the eligibility requirements, namely validity, practicality, and effectiveness.